Analytical expression for factor of safety of an anchored rock slope against plane failure - Shukla S.K.; Hossain Md.M. (My University, 2025)
This paper presents a generalized analytical expression for the factor of safety of an anchored rock slope against plane failure, incorporating most of the practically occurring destabilizing forces. Some of the special cases of this general expression based on possible field situations have been presented in similar forms in the literature. The analysis of the new expression shows that the factor of safety of the rock slope against plane failure increases nonlinearly with an increase in angle of shearing resistance of the joint material, whereas an increase in its cohesion results in a linear increase. For determining a critical factor of safety, the direction of the inertial seismic force should be considered vertically downward. Since the values of shear strength parameters of the joint material, surcharge, water pressure and the stabilizing force govern the factor of safety significantly, it is essentially required to consider their realistic values based on the actual field conditions in the stability analysis. J. Ross Publishing, Inc. © 2011